Analysis of contrast sensitivity in patients implanted with Acunex Vario and LuxSmart extended depth of focus (E-DOF) intraocular lenses (IOLs) - Boryana Irinkova; Irina Kuneva; Iva Petkova (Biotechnology & Biotechnological Equipment)
The aim of this study was to track and analyze preoperative and postoperative contrast sensitivity in patients implanted unilaterally or bilaterally with extended depth of focus intraocular lenses. In the study were included 46 eyes/43 patients. Of these, the control group was 10 subjects, 10 were implanted with a LuxSmart IOL (12 eyes) and 23 with Acunex Vario (24 eyes) with an observation period from 20 June 2023 to 01 September 2023. The contrast sensitivity of all subjects was tested preoperatively and at the first month postoperatively with the RM-800 CONTRAST SENSITIVITY FUNCTION TESTER under photopic and mesopic conditions. Additionally, best-corrected visual acuity for medium (80 cm) and far distance was assessed pre- and post-operation. Both groups showed significant improvement in contrast sensitivity postoperatively. In our study, the Acunex Vario group demonstrated superior contrast sensitivity under photopic and mesopic conditions postoperation. When comparing the CS between the two types of E-DOF IOLs no statistical difference was established. The control group implanted with a standard aspherical monofocal IOL showed better CS compared to bought E-DOFs, all subjects showed improved visual acuity post-operation. The Acunex Vario and LuxSmart E-DOF IOLs both have an improvement in contrast sensitivity and visual acuity postoperatively. The choice between these IOLs may be guided by the surgeons’ preferences and experience as well as the patient’s lifestyle and specific visual needs. Further long-term studies with a larger subject population are recommended to validate these findings.